1968
DOI: 10.1677/joe.0.0410439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Folic Acid on Superovulation in the Immature Rat

Abstract: The effects of the folic acid antagonist, 4-amino-N10-methylpteroylglutamic acid (methotrexate), and varying doses of folic acid were studied on superovulated immature rats. Methotrexate and folic acid were used alone and in combination with oestrone.The parameters selected for study were organ weights and ovum counts. The administration of methotrexate (200 \g=m\g./rat), folic acid (400 \g=m\g.) or oestrone (500 \g=m\g.)partially inhibited ovulation. When given in combination with oestrone, both methotrexate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The question of a possible effect of folic acid on ovarian function was raised in the late 1960s, when it has been shown that in immature superovulated rats, either excess or deficiency of folates partially inhibited ovulation (Willmott et al, 1968). In rhesus monkeys, a folate-restricted diet led to irregular menstrual cycles, whereas pre-ovulatory serum estradiol as well as midluteal progesterone concentrations decreased progressively when compared with animals under normal diet.…”
Section: Folates and Female Fertilitymentioning
confidence: 99%
“…The question of a possible effect of folic acid on ovarian function was raised in the late 1960s, when it has been shown that in immature superovulated rats, either excess or deficiency of folates partially inhibited ovulation (Willmott et al, 1968). In rhesus monkeys, a folate-restricted diet led to irregular menstrual cycles, whereas pre-ovulatory serum estradiol as well as midluteal progesterone concentrations decreased progressively when compared with animals under normal diet.…”
Section: Folates and Female Fertilitymentioning
confidence: 99%
“…Folic acid supplementation has been found to increase litter size in pigs (26). In addition, experimentally induced folate deficiency has resulted in decreased ovulation in rats (27).…”
Section: Figurementioning
confidence: 99%
“…There are reports of animal models evaluating the effects of micronutrient defi ciencies on ovulatory function as early as the 1960s [ 7 ] and prospective studies in humans evaluating the role of other dietary factors on fertility since the 1980s [ 8 ]. Most of the existing literature revolves around the potential role of two purported reproductive toxicants on fertility, caffeine, and alcohol, and is plagued with poor quality research.…”
Section: Diet and Female Fertilitymentioning
confidence: 99%
“…This pathway has a greater relevance when folate requirements are heightened due to increased demand for DNA synthesis such as gametogenesis and early embryo development [ 70 , 71 ]. As early as the 1960s, it was shown in the immature superovulated rat that either an excess or defi ciency of folates partially inhibited ovulation [ 7 ]. In rhesus monkeys, folate restriction results in irregular menstrual cycles, progressive depletion of ovarian granulosa cells, and decreased preovulatory serum estradiol and mid-luteal progesterone [ 72 ].…”
mentioning
confidence: 99%